Understanding and Responding to the Complaining Behaviors of Restaurant Customers from Collectivist Cultures - Bendegul Okumus (Journal of Tourismology)
This paper aims to examine how frontline employees in individualistic cultures such as the United States can better understand and respond to the complaining behaviors of restaurant consumers from collective cultures such as those from Asian countries. Previous studies suggest that customers from collectivist cultures often prefer not to complain directly and openly about service failures. They may offer indirect hints and information to their families and friends about their experiences. It is possible that frontline employees from individualistic cultures may not fully understand the complaining behaviors of restaurant customers from collectivist cultures. This may result in loss of business, customers’ disloyalty and negative publicity about the business. Based on a review of previous research studies in this area, this study offers specific recommendations for practice and future research.